2016
DOI: 10.1161/circresaha.116.309004
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Immunoglobulin E Levels as a Marker of Doxorubicin- and Trastuzumab-Associated Cardiac Dysfunction

Abstract: Rationale There is a critical need to develop robust, mechanistic strategies to identify patients at increased risk of cancer therapeutics-related cardiac dysfunction (CTRCD). Objective We aimed to discover new biomarkers associated with doxorubicin and trastuzumab-induced CTRCD using high-throughput proteomic profiling. Methods and Results Plasma, echocardiograms, and clinical outcomes were collected at standardized intervals in breast cancer patients undergoing doxorubicin and trastuzumab cancer therapy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 25 publications
1
47
0
1
Order By: Relevance
“…The importance of energy metabolism was also confirmed in daunorubicin-induced cardiotoxicity, with alterations in mitochondrial proteins involved in oxidative phosphorylation and energy channeling along with increased proteins involved in autophagy, membrane repair, and apoptosis (20). Small human studies have also suggested the importance of the immune system in the pathophysiology of cardiotoxicity (21). Nevertheless, findings from proteomic studies are still largely preliminary.…”
Section: Proteomicsmentioning
confidence: 99%
“…The importance of energy metabolism was also confirmed in daunorubicin-induced cardiotoxicity, with alterations in mitochondrial proteins involved in oxidative phosphorylation and energy channeling along with increased proteins involved in autophagy, membrane repair, and apoptosis (20). Small human studies have also suggested the importance of the immune system in the pathophysiology of cardiotoxicity (21). Nevertheless, findings from proteomic studies are still largely preliminary.…”
Section: Proteomicsmentioning
confidence: 99%
“…In both studies, an increase of the protein serum amyloid A was observed. In the case of cardiovascular biomarkers, the timespan varies from minutes when studying novel candidates for early myocardial injury, to hours or months when studying markers of cardiac dysfunction. In this last study, among the 1000 proteins identified in different case/control patients, immunoglobulin E was the protein with the largest differences between cases and controls.…”
Section: Protein Expressionmentioning
confidence: 99%
“…Beer et al, 3 in this issue of Circulation Research, have taken an alternative agnostic approach to identify biomarkers that might be used to evaluate risk for chemotherapy-associated cardiac injury and heart failure. Serial plasma samples were collected from a carefully characterized group of breast cancer patients treated with anthracycline and trastuzumab.…”
Section: Article See P 1135mentioning
confidence: 99%